SARCASM IN THE COMMENTS COLUMN OF VIRGOUN'S INSTAGRAM ACCOUNT - Rahmadani, Pesilia; Ningsih, Asih Ria (Jurnal Ilmu Pendidikan Ahlussunnah, 2025)
Language is a very important factor in everyday life. Language as a complement in communicating with the opposite sex both in groups and individually. Communication can be established when a speaker interacts with his interlocutor in community life. Language also plays the most important role in developing social media. In the application of social media, language is used as a form of communication and conveying data. This makes spoken language used to speak directly can become written language. Therefore, the use of written language with a sarcastic style of language arises. One way of communicating that often occurs and is often used by society is sarcasm, which expresses ideas or opinions through various forms of expression containing satire, criticism and ridicule. Sarcasm often occurs in community life. One of them is the use of sarcasm on Instagram accounts, precisely in the comments column. The purpose of this study was to describe the form of netizen sarcastic language in the comments of the virgoun Instagram account. The method used is a qualitative descriptive method. Based on the results of the research conducted, the netizens' sarcastic language in Virgoun's Instagram account comments found 116 data in the form of words, phrases, clauses and sentences.